Observational study on factors related to health-promoting community activity development in primary care (frAC Project): a study protocol. Issue 3 (14th May 2012) - March, Sebastià; Ripoll, Joana; Ruiz-Giménez, Juan Luís; Montaner Gomis, Isabel; Benedé Azagra, Carmen Belén; Elizalde Soto, Lázaro; Vidal, Mª Clara; Bauzà Amengual, M de Lluc; Planas Juan, Trinidad; Maria Pérez Mariano, Damiana; Llull Sarralde, Micaela; Bajo Viñas, Rosa; et al.
Abstract : Introduction: According to Spanish health regulations, primary care professionals have the responsibility to carry out health-promoting community activities (CAs). However, in practice, their implementation is not as widespread as it should be. The aims of this study were to identify factors within the team, the community and the professionals that influence the development of these activities and to describe the community interventions in progress. Methods and analysis: This study is an observational analytical retrospective study. The information will be collected from five Spanish regions: Catalonia, Madrid, the Balearic Islands, Navarra and Aragón. The authors will contact primary care teams (PCTs) and identify the CAs from the previous year. The research team will conduct a peer review whether the inclusion criteria are met. In the health centres where CAs are implemented, the authors will select professionals carrying them out and randomly select an identical number of professionals not doing these activities. In the centres where no CA is implemented, three professionals will be randomly selected. The selected professionals will complete the questionnaires for individual-level variables. Information about the registered population and the PCTs will be collected through questionnaires and secondary sources. Outcomes: Variables will be collected from the community, the PCTs, the individual professionals and CAs. Analysis: A descriptive analysis of all the variables will be carried out, along with a bivariate and a logistic regression analysis, with CAs being the primary outcome. Ethics and dissemination: This study has been approved by the Research Ethics Committee of the Jordi Gol y Gurina Foundation in Barcelona and area 11 in Madrid. The questionnaire distributed to the professionals will be anonymous.